Effectiveness of Cognitive Behavioral Therapy on Internet Addiction in Adolescents with Depressive Symptoms - Salehi, Alireza; Atadokht Haji Siflo, Akbar; Razavi Dole Malal, Seyed Babak (International Journal of Education and Cognitive Sciences, 2026)
Purpose: The present study aimed to investigate the effectiveness of cognitive behavioral therapy (CBT) on internet addiction in adolescents exhibiting symptoms of depression. Methods and Materials: The research employed a quasi-experimental method with a pre-test–post-test control group design. The statistical population consisted of 4,137 secondary school students (lower and upper levels) in Khalkhal County during the 2024–2025 academic year who exhibited depressive symptoms. From this population, 40 participants were selected. Participants were chosen through convenience sampling and were randomly assigned to either the experimental group (n = 20) or the control group (n = 20). Data were analyzed using univariate analysis of covariance (ANCOVA). Findings: The findings indicated that cognitive behavioral therapy was effective in reducing internet addiction among adolescents. Conclusion: These results carry implications for counseling interventions targeting adolescents with depressive symptoms.